PELATIHAN PENGGUNAAN INTERNET SEBAGAI MEDIA PENELUSURAN SUMBER PUSTAKA BAGI GURU-GURU PENDIDIKAN KEWARGANEGARAAN SE-KOTA YOGYAKARTA - Murdiono, Mukhamad (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2010)
In an era of increasingly advanced technologies such as the Internet now has a very large benefits for education. Internet is helping the  education world because with the internet can be obtained the latest information from around the world. Conditions of Teachers in Indonesia today, most still have not mastered the internet. It was due to limited computer facilities owned by the school. If there are computers at school, but there is no internet facility. Internet is actually very helpful for teachers to obtain a source of teaching materials so the materials given to students is the latest material. Because the importance of mastering the Internet for teachers, it is necessary to run training for using the Internet as a media resource library search. Method  community service  activities are carried  out  with the direct method of lecture followed by practice. The need to practice on the use of the Internet is because without the direct practice of training the use of the Internet as a media resource library search will be less useful. This training was attended by 19 teachers from 30 civic education teachers as an invited Yogyakarta city. Goal of community service activities are civic education teachers of junior secondary schools in Yogyakarta city. The results of these activities greatly helped the teachers and get information on the use of the Internet, especially as the media libraries search source. Civic education teachers of junior secondary schools in Yogyakarta city as a follow this training activity find it helpful to obtain materials that can be used to teach his students. Thus they not only use the textbook only as a source of learning. This training is expected to be hyper another teacher to master the use of the Internet, and can help teachers to obtain source materials from the Internet.